The Effect of Adenovirus-Mediated Gene Expression of FHIT in Small Cell Lung Cancer Cells - Zandi, Roza (2011)
The candidate tumor suppressor fragile histidine traid (FHIT) is frequently inactivated in small cell lung cancer (SCLC). Mutations in the p53 gene also occur in the majority of SCLC leading to the accumulation of the mutant protein. Here we evaluated the effect of FHIT gene therapy alone or in combination with the mutant p53-reactivating molecule, PRIMA-1(Met)/APR-246, in SCLC. Overexpression of FHIT by recombinant adenoviral vector (Ad-FHIT)-mediated gene transfer in SCLC cells inhibited their growth by inducing apoptosis and when combined with PRIMA-1(Met)/APR-246, a synergistic cell growth inhibition was achieved.